2016
DOI: 10.1002/wcm.2723
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and performance analysis of dynamic spectrum sharing between DSRC and Wi‐Fi systems

Abstract: The Notice of Proposed Rulemaking 13‐22 released by Federal Communications Commission unlocks the Dedicated Short Range Communication (DSRC) spectrum for Wi‐Fi availability, which undoubtedly brings unpredictable effects to the new‐emerging vehicular applications and services. To efficiently harmonize the spectrum operation between DSRC and Wi‐Fi networks, several dynamic spectrum‐sharing schemes are already proposed to improve the spectral efficiency over a limited bandwidth situation and as well to satisfy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In [26], Wang et al analyzed the influence of communication system and environmental parameters for spectrum efficiency and data rate using various spectrum sharing schemes in an environment that shares the spectrum of DSRC and Wi-Fi system. From the analysis result, they showed that SNR, CW size and especially DSRC node density are a key factor for that performances.…”
Section: Field Test Resultsmentioning
confidence: 99%
“…In [26], Wang et al analyzed the influence of communication system and environmental parameters for spectrum efficiency and data rate using various spectrum sharing schemes in an environment that shares the spectrum of DSRC and Wi-Fi system. From the analysis result, they showed that SNR, CW size and especially DSRC node density are a key factor for that performances.…”
Section: Field Test Resultsmentioning
confidence: 99%
“…The authors concluded that both proposed mechanisms suffered from a delayed detection problem. Other research work that focused on the coexistence of Wi-Fi and 802.11p and evaluated the performance mainly using simulation and analytical modeling includes Naik et al ( 20 ), Khan and Harri ( 21 ), Lansford et al ( 22 ), Wang et al ( 23 ), and Park and Kim ( 24 ).…”
Section: Related Workmentioning
confidence: 99%
“…Other researchers [41] compared four dynamic spectrum sharing schemes involving Wi-Fi and DSRC: non-sharing, original sharing, Qualcomm proposal, and Cisco proposal. The Cisco proposed scheme is similar to the original sharing proposal, sharing up to channel 181 for the 20 MHz bandwidth and up to channel 177 for other bandwidths, but with band priority in DSRC.…”
Section: A Dsrc Onlymentioning
confidence: 99%